Skyrmionic spin structures in layered Fe5GeTe2 up to room temperature - Schmitt, Maurice; Denneulin, Thibaud; Kovács, András; Saunderson, Tom G.; Rüßmann, Philipp; Shahee, Aga; Scholz, Tanja; Tavabi, Amir H.; Gradhand, Martin; Mavropoulos, Phivos; Lotsch, Bettina V.; Dunin-Borkowski, Rafal E.; et al. (2022)
The role of the crystal lattice, temperature and magnetic field for the spin structure formation in the 2D van der Waals magnet Fe5GeTe2 with magnetic ordering up to room temperature is a key open question. Using Lorentz transmission electron microscopy, we experimentally observe topological spin structures up to room temperature in the metastable pre-cooling and stable post-cooling phase of Fe5GeTe2. Over wide temperature and field ranges, skyrmionic magnetic bubbles form without preferred chirality, which is indicative of centrosymmetry. These skyrmions can be observed even in the absence of external fields. To understand the complex magnetic order in Fe5GeTe2, we compare macroscopic magnetometry characterization results with microscopic density functional theory and spin-model calculations. Our results show that even up to room temperature, topological spin structures can be stabilized in centrosymmetric van der Waals magnets.